Resistance, tolerance and environmental transmission dynamics determine host extinction risk in a load‐dependent amphibian disease. (25th July 2017) - Wilber, Mark Q.; Knapp, Roland A.; Toothman, Mary; Briggs, Cheryl J.
Abstract: While disease‐induced extinction is generally considered rare, a number of recently emerging infectious diseases with load‐dependent pathology have led to extinction in wildlife populations. Transmission is a critical factor affecting disease‐induced extinction, but the relative importance of transmission compared to load‐dependent host resistance and tolerance is currently unknown. Using a combination of models and experiments on an amphibian species suffering extirpations from the fungal pathogen Batrachochytrium dendrobatidis (Bd), we show that while transmission from an environmental Bd reservoir increased the ability of Bd to invade an amphibian population and the extinction risk of that population, Bd‐induced extinction dynamics were far more sensitive to host resistance and tolerance than to Bd transmission. We demonstrate that this is a general result for load‐dependent pathogens, where non‐linear resistance and tolerance functions can interact such that small changes in these functions lead to drastic changes in extinction dynamics.